Primary percutaneous coronary intervention in CAD patients: A comparison of major adverse cardiovascular events of second- and third-generation drug-eluting stents - Bibi, Salma; Khan, Amjad; Khan, Amer Hayat; Khan, Muhammad Niaz; Mushtaq, Saima; Rashid, Sheikh Abdur (Frontiers in Pharmacology, 2022)
Background: Biodegradable polymer (BP) drug-eluting stents (DES) have been introduced as a novel solution to the problems of durable polymer (DP) stents. In Pakistan, very few studies are available for the treatment intervention in post-primary percutaneous coronary intervention (PPCI) patients. Our study will compare the major adverse cardiovascular events (MACEs) and their predictors in patients with coronary artery disease (CAD) undergoing PPCI with second- or third-generation DES. Methodology: An observational, retrospective, cohort study was carried out on CAD patients undergoing PPCI with either second- (DP-XIENCE Prime/XIENCE Xpedition) or third-generation (BP-BioMatrix NeoFlex/BioMatrix Alpha) DES. MACEs were assessed after 1 year of PPCI procedure in 341 patients and screened as per inclusion/exclusion criteria (167 in the second-generation group and 174 in the third-generation group). Results: The number of male patients (86.2%) was more than female patients in our study population. MACEs were reported in 4.19% patients after 1 year duration, and the percentage of MACEs was more in the second-generation DES group (4.77%) than in the third-generation group (3.44%); however, statistical analysis has not found any significant difference (p = 0.534). The rate of myocardial infarction (1.19% vs. 0.57%) and stent thrombosis (1.8% vs. 1.15%) was more in the second-generation DES group. However, restenosis (1.19% vs. 1.15%) and cardiac death (0.59% vs. 0.57%) were almost same in both groups. A significant association was found between MACEs and diabetes mellitus (p = 0.025), hypertension (p = 0.035), smoking (p = 0.008), and a family history of CAD (p = 0.018). Conclusion: BP-BioMatrix and DP-XIENCE DES have comparable clinical outcomes. Findings of the current study will assist the policy makers and healthcare providers in the rationalization of scarce resources and evidence-based patient care. However, longer follow-up studies are required for convincing results.